REDESAIN GEDUNG PERPUSTAKAAN DAERAH TOBELO DENGAN MEMBANDINGKAN EFISIENSI KOLOM PERSEGI DAN KOLOM BULAT: (Perbandingan Efisiensi Biaya Kolom) - Kefas V. T. Hendrik; N.A.R.A Mamarimbing; Jeffrey A. Delarue, (Sustainable Construction (SUSCON), 2023)
In developing high-rise buildings in Indonesia, we often find that the main structure used in multi-story buildings is a columnar structure with a square cross-section. Very rarely do we find multi-storied buildings that use a round-section column structure. Thi's the background of this research to determine the level of cost efficiency comparison in rectangular and circular columns. Process Analysis of the cost efficiency of making a rectangular column with a crosssectional dimension of 60 cm x 60 cm costs Rp. 4,619,731, and for the cost of making circular columns with the same cross-sectional area dimensions, namely a diameter of 67 cm, the required cost is Rp. 6,637,566. Thus the rectangular column is more efficient in manufacturing costs with a price difference of Rp. 2,017,835 rupiahs.